2004
DOI: 10.1111/j.1399-0039.2004.000172.x
|View full text |Cite
|
Sign up to set email alerts
|

Promoter polymorphism of SLC11A1 (formerly NRAMP1) confers susceptibility to autoimmune type 1 diabetes mellitus in Japanese

Abstract: Defective function of antigen-presenting cells has been postulated to be one of the non-HLA-linked susceptibility factors for type 1 diabetes mellitus, though the underlying genetic factors remain unclear. SLC11A1 (formerly NRAMP1), a divalent cation transporter, plays a crucial role in macrophage activation. We performed a case-control study in 224 healthy and 95 type 1 diabetic Japanese subjects, examining the length polymorphisms in the promoter region (-377 to -222) of SLC11A1, which may influence transcri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
1
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 33 publications
0
29
1
1
Order By: Relevance
“…Polymorphisms in the genomic region of human NRAMP1 are associated with the risk of atopy in BCG-vaccinated children [23]. Moreover, the Nramp1 gene is involved in several other diseases of deregulated immunity: a polymorphism in the promoter region of NRAMP1 has been associated with inflammatory bowel disease [24], rheumatoid arthritis [25], multiple sclerosis [26] and type 1 diabetes mellitus [27].…”
Section: Infectious Agents and The Hygiene Hypothesismentioning
confidence: 99%
“…Polymorphisms in the genomic region of human NRAMP1 are associated with the risk of atopy in BCG-vaccinated children [23]. Moreover, the Nramp1 gene is involved in several other diseases of deregulated immunity: a polymorphism in the promoter region of NRAMP1 has been associated with inflammatory bowel disease [24], rheumatoid arthritis [25], multiple sclerosis [26] and type 1 diabetes mellitus [27].…”
Section: Infectious Agents and The Hygiene Hypothesismentioning
confidence: 99%
“…Several studies demonstrated NRAMP1 to be related to susceptibility to RA [11][12][13]. The associations of NRAMP1 with other immune-mediated diseases, including juvenile rheumatoid arthritis, type 1 diabetes, multiple sclerosis, and Crohn's disease have also been demonstrated [14][15][16][17][18][19]. NRAMP1 was also associated with behavioral and immune response to stress [20].…”
Section: Introductionmentioning
confidence: 95%
“…It seems clear that SLC11A1 polymorphisms are associated with susceptibility to infectious and autoimmune diseases in human (7,40,53). In the promoter region of SLC11A1, seven different alleles (alleles 1 to 7) of the polymorphism containing a functional Z-DNA-forming repeat have been reported for different populations.…”
mentioning
confidence: 99%